Mathematical Problem Solving Ability of Vocational School Students Reviewed from Self Regulated Learning in Selective Problem Solving (SPS) Assisted Learning Management System (LMS) Learning - Widiyanto, Endra Bagus; Isnarto, Isnarto; Nur Cahyono, Adi (Unnes Journal of Mathematics Education Research, 2021)
Problem-solving abilities are one of the five standards of mathematical ability that students must have (NCTM). This study aims to describe the ability to solve mathematical problems in LMS-assisted SPS learning in terms of self-regulated learning (independent learning). The research method used is a mixed method with a concurrent embedded design method. This research was conducted at SMK Negeri 1 Bawen in the academic year 2019/2020. The subjects in this study were students of class XI which consisted of one experimental class with LMS assisted SPS learning and one control class. In the experimental class, two students were chosen from high, medium and low levels of independence. Hypothesis testing uses the proportion test, the average completeness test, the proportion difference test and the average difference test. The results showed that students with high learning independence could carry out each stage of problem solving well, students with moderate learning independence could carry out each stage of problem solving well but some stages were sometimes missed, while students with low learning independence could not carry out all complete problem-solving stages so that you cannot find a solution to the problem correctly.